Clinicopathological features of progressive renal involvement in TAFRO syndrome: A case report and literature review. Issue 40 (October 2017) - Tanaka, Mari; Tsujimoto, Hiraku; Yamamoto, Kojiro; Shimoda, Saeko; Oka, Kazumasa; Takeoka, Hiroya
Abstract: Rationale: TAFRO syndrome is a systemic inflammatory disease characterized by a constellation of symptoms: Thrombocytopenia, Anasarca, MyeloFibrosis, Renal dysfunction, and Organomegaly. Progressive renal insufficiency is a predominant symptom; however, the mechanism of acute kidney injury (AKI) remains unclear, probably because severe thrombocytopenia prevents kidney biopsy. We report a rare case of TAFRO syndrome with histologically confirmed renal involvement. Patients concerns: A 70-year-old man developed fever, anasarca, AKI, thrombocytopenia, and hepatosplenomegaly. Diagnoses: Plasma vascular endothelial growth factor and serum interleukin-6 levels were significantly elevated. The diagnosis of TAFRO syndrome was made based on his clinical and laboratory findings. Kidney biopsy was performed for the evaluation of AKI and provided a diagnosis of membranoproliferative glomerulonephritis–like lesions due to endothelial injury. Glomerular capillary lumens were extremely narrowed or occluded by endothelial swelling, and marked widening of the subendothelial space by electron-lucent material resulted in mesangiolysis and a double-contoured glomerular basement membrane with no immune complex deposits. Interventions and Outcomes: The patient required temporary hemodialysis due to oliguric AKI, but steroid therapy rapidly improved renal function. Lessons: Typically, patients with progressive renal involvement in TAFRO syndrome rapidly develop oliguric or anuric AKI. This report suggests that the reduction of glomerular perfusion by glomerular endothelial injury might be a primary factor in the progressive AKI of TAFRO syndrome. Our case and the literature review indicate that steroid and/or biological therapies result in highly favorable renal outcomes in patients with progressive AKI in TAFRO syndrome.